2004
DOI: 10.1088/0305-4470/37/26/014
|View full text |Cite
|
Sign up to set email alerts
|

Quantum entanglement in second-quantized condensed matter systems

Abstract: The entanglement between occupation-numbers of different single particle basis states depends on coupling between different single particle basis states in the second-quantized Hamiltonian. Thus in principle, interaction is not necessary for occupation-number entanglement to appear. However, in order to characterize quantum correlation caused by interaction, we use the eigenstates of the singleparticle Hamiltonian as the single particle basis upon which the occupation-number entanglement is defined. Using this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 47 publications
(53 reference statements)
3
46
0
Order By: Relevance
“…This has been exemplified in (Vedral, 2003) (see also Shi, 2004) for the case where the scattering strength is independent of the momentum transfer q:…”
Section: Entanglement In Itinerant Bosonic Systemsmentioning
confidence: 89%
See 2 more Smart Citations
“…This has been exemplified in (Vedral, 2003) (see also Shi, 2004) for the case where the scattering strength is independent of the momentum transfer q:…”
Section: Entanglement In Itinerant Bosonic Systemsmentioning
confidence: 89%
“…This line has been followed in (Shi, 2004; for analyzing a connection to BCS superconductivity and also to the phenomenon of η-pairing, a possible scenario for high T c superconductivity (see also Fan et al, 2004;Vedral, 2004a,b). Such states appear as eigenstates of the Hubbard model with off diagonal long range order (see III.B).…”
Section: Pairing Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the spatial entanglement of quantum states reveals the non-local properties of many-body wave functions 8,9 which naturally suggests its usefulness for identifying localized and delocalized states. Additionally, entanglement is particularly useful in capturing universal properties that cannot be obtained through the expectation value of local operators 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…With these recognitions, it is found that modes, rather than particle labels, are universal concepts to properly describe the quantum entanglement of indistinguishable * Electronic address: songtc@nankai.edu.cn particle systems. This idea is used to characterize the ground-state entanglement of the BCS model [24] and superconductivity [23,29], and also it is investigated to derive the interesting relation between entanglement and quantum state transfer [30]. Some related works were also proposed by different authors [25,26,27,28] recently.…”
Section: Introductionmentioning
confidence: 99%